Influence of heavy metals on an environment and health of population - Mukasheva, M.A.; Nugumanova, Sh.M.; Surzhikov, D.V. (Pub KSU, 2016)
The literary analysis of influence of heavy metals is Given on an environment and organism of man. Heavy metals are the basic pollutants of environment of industrial cities. Connections of heavy metals possess high biochemical activity, ability to accumulate in an environment and living organisms. The important role of microelements is educed as catalysts of many biological reactions and pathogenic influence of heavy metals on the organism of man. The basic sources of receipt of heavy metals in an environment are extrass of industrial enterprises and exhausts of motor transport. The high concentrations of heavy metals in an environment can result in the decline of adaptive reactions of organism and development of the sickly states.
Ауыр металдардың қоршаған ортаға жəне халықтың денсаулығына əсері
Влияние тяжелых металлов на окружающую среду и здоровье населения
Keywords: contamination; influence; factors; environment; heavy metals are lead; zinc; cadmium; concentration; level; toxic influence